Модель поширення ультразвукових хвиль в плинному середовищі - Білинський, Йосип Йосипович; Гладишевський, Микола Володимирович; Бурдейний, Валентин Борисович (НТУ "ХПІ", 2016)
В роботі проведено дослідження особливостей розповсюдження акустичних хвиль ультразвукового діапазону в плинному середовищі. Дослідження дало змогу розробити модель розповсюдження ультразвукових хвиль в межах ближньої зони. Детальний аналіз розповсюдження хвиль дало змогу встановити тиск ультразвукової хвилі на приймачі, залежно від швидкості потоку та частоти коливань. Таким чином, результати моделювання дозволили зробити висновок про можливість розробки метода вимірювання швидкості потоку на основі використання ближньої зони ультразвукового перетворювача.

This article shows the research done upon characteristics of acoustic waves propagation in ultrasonic range of frequencies in flowing medium. As of today, such research is motivated not so much as scientific interest as practical need. And this need explained as that ultrasonic waves is a good tool in solving wide range of technical and scientific tasks. Longitudinal and transversal waves, that are being distributed through medium as acoustic waves are the waves of small volumetric change (longitudinal waves) and waves of deformation without volume change (transversal waves). Speed of acoustic wave propagation (speed of sound) depends on if the waves are longitudinal or transversal not only on medium. Volume change that is caused by propagation of longitudinal waves is given as pressure change in a medium. This pressure change due to wave propagation in the point is defined as acoustic pressure. Picture 1 (a) shows function change along x axis. This function creates number of oscillations where x tends to increase. When it reaches its last maximum and then slowly goes down. And the area in which function |I| creates oscillations is called as near zone. On Picture 3 dependency graph of function |I| on flow rate andultrasonic wave frequency is shown. From the graph can be seen that only in some relations of flow rate and frequency function |I| reaches its maximum value. Based on this modulation the next one became possible which is shown on Picture 4 and represents the dependence of acoustic pressure on flow rate and frequency. Equation 6 represents a mathematical model of ultrasonic wave propagation in flowing medium, which shows how signal behaves in the near zone due to the frequency and flow rate change. The simulation results allow concluding the possibility of developing a new method for flow rate measurement based on use of near zone of ultrasonic propagation.
Model of distribution of ultrasonic waves in flowing medium
Keywords: ультразвукові коливання; ближня зона; тиск звукової хвилі; швидкість потоку; ультразвуковий перетворювач; ultrasonic waves; near zone; sound wave pressure; flow rate; ultrasonic wave frequency